Association between Helicobacter pylori infection and serum thyroid stimulating hormone in the National Health and Nutrition Examination Survey 1999-2000 - Wang, Jinyun; Liu, Dingwei; Xie, Yong (Frontiers in Endocrinology, 2022)
Objective: Current evidence on the associations between plasma thyroid stimulating hormone (TSH) and Helicobacter pylori (H. pylori) infection is conflicting. Therefore, this study aimed to examine TSH in relation to H. pylori infection. Methods: A retrospective cross-sectional study was conducted with 948 subjects aged 30-85 years in the US National Health and Nutrition Examination Survey (NHANES) 1999–2000. Binary logistic regression models were performed to evaluate the associations between H. pylori seropositivity and TSH. Subgroup analyses stratified by sex, age, and body mass index (BMI) were performed. Results: The serum TSH was higher in subjects with H. pylori seropositive than those with H. pylori seronegative. A significant positive association was found between H. pylori seropositivity and TSH with increasing quartiles of hormonal levels in univariate regression models (Q4 vs Q1: OR = 1.659; 95% CI, 1.152-2.389) and in multivariate regression models (Q4 vs Q1: OR = 1.604; 95% CI, 1.087-2.367). In stratified analyses, the adjusted association of serum TSH with H. pylori seropositivity was statistically significant in male (Q4 vs Q1: OR = 1.894; 95% CI, 1.109-3.235), normal BMI (Q4 vs Q1: OR = 1.894; 95% CI, 1.109-3.235), overweight (Q4 vs Q1: OR = 2.124; 95% CI, 1.047-4.308;), obese (Q4 vs Q1: OR = 0.429; 95% CI, 0.220-0.837), and age over 60 years (Q4 vs Q1: OR = 1.999; 95% CI, 1.118-3.575). Conclusion: Circulating TSH levels were associated with the risk of H. pylori infection, especially among male, overweight and elderly adults.